An Enterobacter cloacae strain NG-33 that can solubilize phosphate and promote maize growth - Chen, Xinxin; Yang, Caihe; Palta, Jairo A.; Li, Youzhi; Fan, Xianwei (Frontiers in Microbiology, 2022)
It is critical to identify and evaluate efficient phosphate-solubilizing bacteria (PSB) that enable P uptake from unavailable forms, and therefore improve the phosphorus (P) uptake efficiency of crops. The Enterobacter cloacae strain NG-33, belonging to PSB, was isolated and identified from calcareous rhizosphere soils in Nonggang National Reserve, Guangxi, China. The stain NG-33 could reduce the pH of the medium to below 5.6, and had the ability to release soluble phosphorus (P; 180.7 μg mL−1) during the culture in the National Botanical Research Institute's Phosphate medium (NBRIP), and produced such organic acids as gluconic acid (4881 mg L−1), acetic acid (346 mg L−1), and indole-3-acetic acid (20.4 μg mL−1). It could also convert inorganic P in AlPO4 (Al-P) and FePO4 (Fe-P) into soluble P, with conversion efficiencies of 19.2 μg mL−1 and 16.3 μg mL−1, respectively. Under pot experiments and when compared controls without inoculating NG-33, the shoot and root biomass of maize seedlings showed increases by 140% for shoot biomass and by 97% for root biomass in loamy soil (P sufficient) inoculated with NG-33. In sandy soil (P deficit) supplemented with tricalcium phosphate and inoculated with NG-33, the soluble P content was significantly higher, 58.6% in soil and 33.6% in roots, meanwhile, the biomass of shoots and roots increased by 14.9 % and 24.9 %, respectively. The growth-promoting effects coupled to the significant increase in leaf net photosynthetic rate and stomatal conductance of plants grown in NG-33-inoculated soil. Inoculating NG-33 could significantly improve the diversity and richness of bacterial population and altered the dominant bacterial population in soil.